Dolutegravir derivative inhibits proliferation and induces apoptosis of non-small cell lung cancer cells via calcium signaling pathway. (November 2020) - Wang, Wen-Jun; Mao, Long-Fei; Lai, Huan-Ling; Wang, Yu-Wei; Jiang, Ze-Bo; Li, Wei; Huang, Ju-Min; Xie, Ya-Jia; Xu, Cong; Liu, Pei; Li, Yue-Ming; Leung, Elaine Lai Han; et al.
Graphical abstract: DTHP, a novel derivative of DTG, inhibits cell proliferation and induces apoptosis of NSCLC cells via the Ca 2+ signaling pathway, leading to the activation of CaMKK / AMPK proteins, excessive ROS production and reduction of mitochondria membrane potential. Abstract: Non-small cell lung cancer (NSCLC) is the most prevalent type of lung cancer. However, there has been little improvement in its cure rate in the last 30 years, due to its intricate heterogeneity and drug resistance. Accumulating evidences have demonstrated that dysregulation of calcium (Ca 2+ ) homeostasis contributes to oncogenesis and promotes tumor development. Inhibitors of Ca 2+ channels/transporters to restore intracellular Ca 2+ level were found to arrest tumor cell division, induce apoptosis, and suppress tumor growth both in vitro and in vivo. Dolutegravir (DTG), which is a first-line drug for Acquired Immune Deficiency Syndrome (AIDs) treatment, has been shown to increase intracellular Ca 2+ levels and Reactive oxygen species (ROS) levels in human erythrocytes, leading to suicidal erythrocyte death or eryptosis. To explore the potential of DTG as an antitumor agent, we have designed and synthesized a panel of compounds based on the principle of biologically active substructure splicing of DTG. Our data demonstrated that 7-methoxy-4-methyl-6, 8-dioxo-N-(3-(1-(2-(trifluoromethyl)phenyl)-1H-1, 2, 3-triazol-4-yl)phenyl)-3, 4, 6, 8, 12, 12a-hexahydro-2H-pyrido[1′, 2′:4, 5]pyrazino[2, 1-b][1, 3]oxazine-9-carboxamide (DTHP), a novel derivative of DTG, strongly inhibited the colony-forming ability and proliferation of NSCLC cells, but displayed no cytotoxicity to normal lung cells. DTHP treatment also induced apoptosis and upregulate intracellular Ca 2+ level in NSCLC cells significantly. Inhibiting Ca 2+ signaling alleviated DTHP-induced apoptosis, suggesting the perturbation of intracellular Ca 2+ is responsible for DTHP-induced apoptosis. We further discovered that DTHP activates AMPK signaling pathway through binding to SERCA, a Ca 2+ -ATPase. On the other hand, DTHP treatment promoted mitochondrial ROS production, causing mitochondrial dysfunction and cell death. Finally, DTHP effectively inhibited tumor growth in the mouse xenograft model of lung cancer with low toxicity to normal organs. Taken together, our work identified DTHP as a superior antitumor agent, which will provide a novel strategy for the treatment of NSCLC with potential clinical application.